EVALUATION OF ROLE OF HER2 EXPRESSION BY IHC IN PREMALIGNANT AND MALIGNANT LESIONS OF THE UTERINE CERVIX - AN INSTITUTIONAL BASED PROSPECTIVE STUDY. - Mitali Dash; Anushuya Dash; Bandana Mishra; Saroj Ranjan Mohanty; Manoj Kumar Patro; Sunita Rani Senapati (Student's Journal of Health Research, 2023)
Background: The most frequent malignancy in Indian women is uterine cervix cancer. According to the clinical stage of the tumour and the surgical findings, surgery is the primary mode of treatment, coupled with radiation and chemotherapy. Despite the use of cisplatin-based combination treatment, patients with advanced or recurring illness have a poor prognosis. In order to replace or supplement the present therapy for these patients, it is becoming more and more important to identify novel therapeutic targets. The goal of the current investigation was to determine whether Her-2/neu expression was present. Methods: In this investigation, 81 cervical specimens were used. These cases included squamous cell carcinoma and adenocarcinoma diagnoses. BioGenex monoclonal mouse anti-human HER-2/neu Receptor IgG1 antibody was used for HER-2/neu immunostaining. Results: Malignant lesions showed higher expression of HER-2/neu compared to premalignant lesions. Additionally, there was a correlation between staining intensity and lymph node metastasis, clinical stage, and malignant tumour grade. Conclusion: Oncoprotein HER-2/neu overexpression has been linked to aggressive biological behaviour, a poor prognosis, and the propensity for metastatic spread.